2015
DOI: 10.1108/ijrdm-06-2013-0128
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of consumer risk perception and innovativeness on online shopping in India

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 89 publications
5
94
1
7
Order By: Relevance
“…Indeed, as Rothwell (1994, p2) states "..at the very heart of the successful innovation process were 'key individuals'… with a strong commitment to innovation". Further, while research into the relationship between individuals and innovation extends back to the late 1960's and early 1970's (eg Nabseth andRay, 1974;Rokeach, 1967) the subject remains a popular focus for projects today with journals still regularly reporting the results of research into the nature of the relationship (eg Hidayanto et al, 2015;Tan and Sie, 2015;Thakur and Srivastava, 2015).…”
Section: Personal Innovativeness and Propensity To Innovatementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as Rothwell (1994, p2) states "..at the very heart of the successful innovation process were 'key individuals'… with a strong commitment to innovation". Further, while research into the relationship between individuals and innovation extends back to the late 1960's and early 1970's (eg Nabseth andRay, 1974;Rokeach, 1967) the subject remains a popular focus for projects today with journals still regularly reporting the results of research into the nature of the relationship (eg Hidayanto et al, 2015;Tan and Sie, 2015;Thakur and Srivastava, 2015).…”
Section: Personal Innovativeness and Propensity To Innovatementioning
confidence: 99%
“…It is apparent that some of the scales have sought to measure Personal Innovativeness as a generic construct (eg Ettlie and O'Keefe, 1982;Goldsmith, 1991;Hurt et al, 1977;Kirton, 1976;Kocak and Onen, 2012;Pallister and Foxall, 1998) while others have sought to measure Personal Innovativeness as a domain specific construct. These specific domains include entrepreneurship (Gibson andGibson, 2011), personality (Jackson, 1976), propensity to change (Hage and Dewar, 1973), innovative purchasing behaviour (Leavitt and Walton, 1975), consumer innovativeness and decision making (Goldsmith and Hofacker, 1991;Goldsmith et al, 1995;Ostlund, 1974), mobile commerce (Kourouthanassis et al, 2014;Lu, 2014;Roca et al, 2010;Thakur and Srivastava, 2015), exploratory behaviour (Baumgartner and Steenkamp, 1996;Raju, 1980), consumers eco-innovation (Jansson, 2011), internet banking (Gounaris and Koritos, 2008;Hidayanto et al, 2015), Information Technology (Agarwal and Prasad, 1998;Jackson et al, 2013;Tan and Sie, 2015;Yi et al, 2006), virtual reality simulations (Fagan et al, 2012), webcasting adoption (Lin, 2006), employee level (Hormiga et al, 2013), social media marketing (Pentina et al, 2014), and mobile learning (Cheng, 2014).…”
Section: Personal Innovativeness and Propensity To Innovatementioning
confidence: 99%
“…Chiejina and Olamide (2014) found the role of "pay-ondelivery" payment option as a major trust builder between Nigerian consumers and online merchants. Thakur and Srivastava (2015) studied the barriers to online shopping and found that consumers do not trust online channels to share their banking details and prefer making payments through COD. Jain (2014) studied the consumer decision-making process in the Indian environment and concluded that the majority of consumers feel secure while shopping online, and the most preferred mode of payment is cash-on-delivery mode of payment.…”
Section: Hypothesis 4 (H4) Customer Satisfaction Will Have a Signifimentioning
confidence: 99%
“…In the future, this tendency will continue thanks to the emergence of the new online markets, especially in Asian countries, such as India [29], Indonesia [31], Taiwan [34], Jordan [1], Iran [12], Malaysia [3], etc. that offer a very interesting growth potential due to their large populations and relatively low e-commerce penetration rate.…”
Section: Introductionmentioning
confidence: 99%